The politicisation of social programmes: insights from Ghana's School Feeding Programme. Issue 7 (3rd October 2022) - Mohammed, Abdul-Rahim
ABSTRACT: The dominant discourses on the politicisation of social policy in the Global South mainly focus on analysing the effects of clientelism through the lens of voting behaviour or electoral outcomes. This paper goes beyond the dominant voting behaviour lens by arguing that the effects of political clientelism go well beyond the scope of electoral outcomes. Using qualitative data from the Ghana School Feeding Programme (GSFP), the paper shows how the programme is used to reward loyal party supporters through the partisan award of service delivery contracts. Further, the paper demonstrates how this politicisation of the programme ultimately leads to a de facto system of no supervision and monitoring of the activities of frontline service providers, undercutting the goals of the GSFP in the long run.